Whitewashing State Capture - Discursive Practices in the Western Balkans - Marjanović Rudan, Ana (Journal of Regional Security, 2022)
Through the use of language, government institutions and officials in elective democracies try to present particular cases of abuse of power and public resources as legitimate and enable similar practices in the future. The research goal in this article is to identify and reveal the strategies used within the Western Balkans’ official discourses to legitimize particular cases of suspected state capture and assess their outcomes. The empirical study of six prominent cases of suspected state capture in construction industry in the period from 2010 to 2020 indicates that a single legitimization strategy is used region-wide, and this article contributes to better understanding it. To assess the strategy outcomes, an original analytic model is proposed. The findings suggest that the deployment of the strategy to legitimize the suspected cases of state capture encourages potential captors in the region to consider engaging in similar practices in the future.
Keywords: discursive institutionalism, discursive strategy, legitimization, state capture, Western Balkans